Structural bioinformatics analysis of the Hsp40 and Hsp70 molecular chaperones from humans - Adeyemi, Samson Adebowale (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2014)
HSP70 is one of the most important families of molecular chaperone that regulate the folding and transport of client proteins in an ATP dependent manner. The ATPase activity of HSP70 is stimulated through an interaction with its family of HSP40 co-chaperones. There is evidence to suggest that specific partnerships occur between the different HSP40 and HSP70 isoforms. While some of the residues involved in the interaction are known, many of the residues governing the specificity of HSP40-HSP70 partnerships are not precisely defined. It is not currently possible to predict which HSP40 and HSP70 isoforms will interact. We attempted to use bioinformatics to identify residues involved in the specificity of the interaction between the J domain from HSP40 and the ATPase domain from the HSP70 isoforms from humans. A total of 49 HSP40 and 13 HSP70 sequences from humans were retrieved and used for subsequent analyses. The HSP40 J domains and HSP70 ATPase domains were extracted using python scripts and classified according to the subcellular localization of the proteins using localization prediction programs. Motif analysis was carried out using the full length HSP40 proteins and Multiple Sequence Alignment (MSA) was performed to identify conserved residues that may contribute to the J domain "“ ATPase domain interactions. Phylogenetic inference of the proteins was also performed in order to study their evolutionary relationship. Homology models of the J domains and ATPase domains were generated. The corresponding models were docked using HADDOCK server in order to analyze possible putative interactions between the partner proteins using the Protein Interactions Calculator (PIC). The level of residue conservation was found to be higher in Type I and II HSP40 than in Type III J proteins. While highly conserved residues on helixes II and III could play critical roles in J domain interactions with corresponding HSP70s, conserved residues on helixes I and IV seemed to be significant in keeping the J domain in its right orientation for functional interactions with HSP70s. Our results also showed that helixes II and III formed the interaction interface for binding to HSP70 ATPase domain as well as the linker residues. Finally, data based docking procedures, such as applied in this study, could be an effective method to investigate protein-protein interactions complex of biomolecules.
Keywords: Structural bioinformatics; Molecular chaperones; Heat shock proteins; Protein-protein interactions; Biomolecules